Dosežki in načrti v raziskovanju slovenskega izseljenstva po znanstvenih disciplinah - Trebše-Štolfa, Milica (Dve domovini, 1993)
Discussion on scientific conference "Achievements and plans in the research of Slovene emigration in scientific disciplines", Ljubljana, 26 May 1992
Keywords: archive records; arhivsko gradivo; emigration; izseljenstvo; Slovene emigrants; slovenski izseljenci